Cold Adaptation Mechanisms of a Snow Alga Chlamydomonas nivalis During Temperature Fluctuations - Peng, Zhao; Liu, Gai; Huang, Kaiyao (Frontiers in Microbiology, 2021)
Cold environments, such as glaciers and alpines, constitute unique habitats for organisms living on Earth. In these harsh ecosystems, snow algae survive, prosper, and even become primary producers for microbial communities. How the snow algae maintain physiological activity when the ambient temperature changes violently remains unsolved. To understand and explore the cold adaptation mechanisms of the unicellular snow alga Chlamydomonas nivalis (C. nivalis), we compared its physiological responses to a reference model organism from the same genus, Chlamydomonas reinhardtii (C. reinhardtii). When both cell types were shifted from 22°C to 4°C, C. nivalis exhibited an apparent advantage in cold tolerance over C. reinhardtii, as C. nivalis had both a higher growth rate and photosynthetic efficiency. To determine the mechanisms underlying cold tolerance in C. nivalis, RNA sequencing was used to compare the transcriptome of the two algal species after 1 h of cold treatment, mimicking temperature fluctuations in the polar region. Differential expression analysis showed that the transcriptome in C. nivalis changed less and was more stable during rapid temperature decrease than in C. reinhardtii, especially for the expression of photosynthesis related genes. We also found that transcription in C. nivalis was precisely regulated by the cold response network, consisting of at least 12 transcription factors and 3 RNA-binding proteins. Moreover, upregulation of genes participating in nitrogen metabolism, the pentose phosphate pathway, and polysaccharide biosynthesis indicated that increasing resource assimilation and remodeling of metabolisms were critical for adaptation to temperature changes in C. nivalis. In addition, we identified horizontally transferred genes differentially expressed in C. nivalis, which are critical for cold adaptation in other psychrophiles. In brief, our results reveal that the snow alga C. nivalis adapts to rapid decrease in temperature by efficiently regulating the transcriptional levels of specific genes to adjust resource assimilation and metabolic pathways, providing critical insight into understanding how snow algae survive and propagate in cold environments.